Prevalence, molecular characterization, and antimicrobial resistance profile of Clostridium perfringens from India: A scoping review. (October 2022) - Yadav, Jay Prakash; Kaur, Simranpreet; Dhaka, Pankaj; Vijay, Deepthi; Bedi, Jasbir Singh
Abstract: Clostridium perfringens is one of the most important foodborne pathogens that causes histotoxic diseases and intestinal infections in both humans and animals. The present scoping review has been designed to analyze the literature published during 2000–2021 from India on the prevalence, molecular characterization, and antimicrobial resistance profile of C. perfringens isolates recovered from humans, animals, animal-based foods, and associated environmental samples. The peer-reviewed articles retrieved from four electronic databases (Google Scholar, PubMed, Science Direct, and Web of Science) were assessed using PRISMA-ScR guidelines. A total of 32 studies from India were selected on the basis of their relevance and inclusion criteria. The overall prevalence of C. perfringens among domestic animals having history of clinical symptoms and among healthy animals was found to be 65.8% (508/772) and 42.8% (493/1152), respectively. The pathogen was also detected in clinically affected wild animals (75%), healthy wild animals (35.4%), and captive birds (24.5%). The detection of C. perfringens among poultry having necrotic enteritis and among healthy birds was found to be 66.8% (321/480) and 25.6% (80/312), respectively. The detection of pathogen among animal-based foods (i.e., meat, milk, and fish and their products) and environmental samples depicted a prevalence of 20.8% (325/1562) and 30.2% (23/76), respectively. However, the prevalence of C. perfringens among humans having history of diarrhea and among healthy humans was found to be 25% (70/280) and 23.2% (36/155), respectively. The genotyping of C. perfringens isolates revealed that toxin type A was found to be the most prevalent genotype. Along with the alpha toxin gene ( cpa ), beta ( cpb ), epsilon ( etx ), iota ( itx ), enterotoxin ( cpe ), beta-2 toxin ( cpb2 ), and NetB ( netB ) toxins were also detected in different combinations. Antimicrobial resistance profile of C. perfringens isolates recovered from different sources demonstrated that the highest resistance was detected against sulphonamides (76.8%) and tetracycline (41.3%) by phenotypic and genotypic detection methods, respectively. Comprehensive scientific studies covering different geographical areas at the human-animal-environment interface are crucial to generalize the real magnitude of C. perfringens- associated problem in India and for establishing a reliable database. Highlights: Molecular epidemiology and antibiogram of C. perfringens from India were investigated. Toxin type A was found to be the most prevalent genotype among genotypes A-G. Carbapenem and lincomycin antibiotics were found to be most effective against C. perfringens. Systemic epidemiological studies within One Health framework are warranted.